Una introducción a la teoría feminista de Roswitha Scholz: El patriarcado capitalista de la forma valor/escisión - Torres Gaxiola, Andrea (2022)
This paper intends to be a short introduction to Roswitha Scholz’s critique of the political economy of gender, as a feminist reading and reformulation of Karl Marx’s labor theory of value. Firstly, we analyze the criticism to traditional marxism that Moishe Postone carries out, as well as Roswitha Scholz’s critique to feminist marxism. We intend to show that Roswitha Scholz critique of value aims to validate gender as a central category for a criticaltheory of capitalism and of the oppression of women. Secondly, we analize the core elements of Roswitha Scholz’s value-dissociation form theory. Lastly, we review its implications and its grasp of the oppression and emancipation of women.